Ecological conceptualization of Halal-Haram divide - Solihu, Abdul Kabir Hussain (Springer: Singapore, 2014)
Halal and haram are evaluative concepts that refer to what is permissible or impermissible, respectively, in Islamic law. When applied to minerals, plants, or animals, the duo refers to what is permissible or impermissible to consume therein. There has been upsurge in the production and proliferation of halal products which enormously serves the Muslim religious as well as economic interests. However, in a world of market-driven economy when market profit often clashes with the environmental interests and safety, there is a need to address halal and haram within a broader ecological framework. In attempt to proffer an alternative modality of appreciating nature and its biodiversity, this study explores symbiotic relations in nature and subsume halal-haram divide under two Qur’anic ecological keywords of rizq (sustenance) and haqq (truth). The study reveals that, ecologically conceptualized, haram things are simply haram for humans to consume or to make a direct contact with, but not necessarily haram for other nature’s constituents upon which human existence and sustenance depend.